Femoral Shaft Fracture with Popliteal Artery Injury: A Case Report of a Gunshot Wound - Maillard, Noémie Fourcroy; Souza, Flávia Nunes Benicio de; Santos, João Alexandre Ranzeiro de Bragança dos; Souza, Julia Habibe de; Rezende, Manuella Santos de; Mendes, Vinicius Macário; Calsoni, José Antônio Vieira da Silva; Bahia, Frederico do Amaral; Rosati, Ana Paula de Carvalho Miranda; Rosati, Luis Fernando (Brazilian Journal of Case Reports, 2024)
This study reports the case of a 28-year-old male patient with a femoral shaft fracture and popliteal artery injury following a gunshot wound. Initial evaluation revealed the absence of pedal pulse and delayed capillary refill, with radiography performed to confirm the fracture and Doppler ultrasound for vascular assessment. The patient had a dynamic condylar screw (DCS) plate installed during a previous surgery, adding complexity to the treatment. Surgical intervention included repair of the femoral artery and vein and popliteal artery anastomosis. This report highlights the importance of early diagnosis, including the use of Doppler ultrasound to detect typical vascular injuries, and a multidisciplinary approach to ensure restored perfusion and prevent postoperative complications.